2021
DOI: 10.3390/cancers13215512
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Deep Sequencing of Mycosis Fungoides Reveals Intracellular Signaling Pathways Associated with Aggressiveness and Large Cell Transformation

Abstract: Introduction: Large-cell transformation (LCT) of mycosis fungoides (MF) has been associated with a higher risk of relapse and progression and, consequently, restricted prognosis. Its molecular pathogenesis has not been elucidated yet. Materials and Methods: In order to address molecular mechanisms of LCT, we performed hybrid capture panel-based sequencing of skin biopsies from 10 patients suffering from MF with LCT versus 17 patients without LCT including follow-up biopsies during clinical course, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
(81 reference statements)
0
3
0
Order By: Relevance
“…tMF was shown to have recurrent activating RAS mutations ( KRAS and NRAS ), mutations in JAK/STAT pathway, and epigenetic regulation genes ( TET2 , DNMT3A, KMT2D , EP300 , EZH2 , and CREBBP ). 9 Another common molecular finding associated with tMF is CDKN2A/CDKN2B deletions, which also serve as an independent predictor of reduced survival, and which might be a useful diagnostic tool in the differentiation of tMF and pcALCL. 10 Although our case did not show similar molecular findings, the NGS study of the lymph node showed mutations in genes commonly altered in MF, including SOCS1 , TP53 , and RB1 , and we believe that these findings support the diagnosis of tMF.…”
Section: Discussionmentioning
confidence: 99%
“…tMF was shown to have recurrent activating RAS mutations ( KRAS and NRAS ), mutations in JAK/STAT pathway, and epigenetic regulation genes ( TET2 , DNMT3A, KMT2D , EP300 , EZH2 , and CREBBP ). 9 Another common molecular finding associated with tMF is CDKN2A/CDKN2B deletions, which also serve as an independent predictor of reduced survival, and which might be a useful diagnostic tool in the differentiation of tMF and pcALCL. 10 Although our case did not show similar molecular findings, the NGS study of the lymph node showed mutations in genes commonly altered in MF, including SOCS1 , TP53 , and RB1 , and we believe that these findings support the diagnosis of tMF.…”
Section: Discussionmentioning
confidence: 99%
“…The overexpression of downstream signaling components like MAPK of cytokine receptors is due to gain-of-function mutation in B-Raf (p. Asp594Asn) and ERK-1 (p. Glu322Ala, p. Glu322lys) in MF subjects (74). In stage IV subjects of MF, mutations were identified in KRAS (Kristen Rat Sarcoma Viral oncogene homolog) and NRAS (Neuroblastoma RAS Viral oncogene homolog) genes (74)(75)(76). Immunohistochemistry studies revealed that in the nucleus of 53% cells of MF lesion, ERK1/2 gets phosphorylated, which has been associated with phospho-4E-BP1 (Eukaryotic Translation Initiation Factor 4E Binding Protein 1) (p-4E-BP1) upregulation.…”
Section: Cytokine and Cell Signaling In The Tumor Microenvironment Of...mentioning
confidence: 99%
“…MF/SS pathogenesis and the mechanisms involved in their progression from early to advanced phases are far from being fully understood [10][11][12]. Different players are involved in MF/SS, such as gene alterations, changes in the microenvironment composition, cytokine balance changes, and transcriptional pathways [10][11][12][13][14][15][16]. All these players are intrinsically linked.…”
Section: Introductionmentioning
confidence: 99%